MoniMoney and Teams Games Tournament: Contextual Learning Innovation to Improve Numeracy Literacy in Elementary Schools - Ruqoyyah, Siti; Savira Wardani, Duhita; Aprianti , Ema; Anggraeni , Ineke (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study was motivated by the low mathematical numeracy literacy skills of elementary school students, particularly in understanding the fractional values of currency. This condition is exacerbated by the limited use of instructional media and the application of unengaging learning models, which fail to promote active student involvement. The aim of this study is to develop the "MoniMoney" instructional media, combined with the Teams Games Tournament (TGT) model, to improve the mathematical numeracy literacy of second-grade elementary students. The study employed the Research and Development (R&D) method based on the Borg & Gall model. The research subjects consisted of 10 students for a limited trial and 22 students for a broader trial. Instruments included field notes, teacher interviews, validation sheets for media and content, as well as pretest and posttest assessments. Data were analyzed using N-Gain calculations and significance testing. The results showed that the MoniMoney instructional media was declared valid and feasible based on expert validation. Its use significantly improved students' mathematical numeracy literacy, with an average N-Gain score of 0.72 (high category). This study concludes that the MoniMoney instructional media, systematically developed and supported by the TGT model, is effective in improving students’ mathematical numeracy literacy. The novelty of this research lies in the integration of Monopoly-style educational media on the topic of fractional currency values with a fun cooperative learning approach, aligned with the characteristics of elementary school students. This media has the potential to serve as an innovative solution for meaningful and contextual numeracy learning.